Development of a decision support system (DSS) for Malaysian adult weight management / Aadilah binti Baharuddin - Baharuddin, Aadilah (2014)
The main objective of this study is to develop an electronic knowledge-based decision support system (DSS) for the use of experts, specifically nutritionists and dieticians, as well as Malaysian adults for effective weight management. The system will allow the user to keep track of their daily food consumption and energy expenditure to prevent them from getting overweight since obesity is a prominent public health problem in Malaysia. It is also in line with goals of the National Plan of Action for Nutrition of Malaysia (NPANM) for the period of 2006 to 2015 to reduce overweight individuals and prevent obesity among Malaysians (MOH, 2006). In order to achieve this objective, implementation of the DSS is based on the System Development Lifecycle (SDLC) method that consists of five phases; (1) Study of the existing system; (2) System requirement and analysis; (3) System design; (4) System implementation and (5) System testing and operation. A usability study was also conducted involving thirty participants consisting of experts and the public using a web-based test instrument. This study is significant in testing and measuring users’ interactions and satisfaction with specific aspects in dealing with the WeightExpert DSS prototype. The results showed that participants' reactions to the WeightExpert DSS prototype were positive, especially with respect to ease of use, straightforwardness, reliability of data bases, and the well-structured design of its interface. However, the study did identify some areas where the usability of the application can be improved, particularly with regard to flexibility of access to the application, storing of daily record for the projected timeline and addition of up food records from Asean countries food databases.